Effects of barley β‐glucan with various molecular weights partially hydrolyzed by endogenous β‐glucanase on glucose tolerance and lipid metabolism in mice. Issue 5 (18th August 2020) - Mio, Kento; Yamanaka, Chiemi; Ichinose, Yasunori; Kohyama, Noriko; Yanagisawa, Takashi; Aoe, Seiichiro
Abstract: Background and objectives: In this study, we investigated whether the intake of a high‐fat diet containing barley β‐glucan partially hydrolyzed by endogenous β‐glucanase (PHEB) for 2 or 8 hr affects glucose metabolism, lipid metabolism, and intestinal microbiota compared with untreated barley (BF) and a control diet in mice. Findings: A significant increase in cecum weight was observed in all barley groups compared with the control group. Liver lipid accumulation was significantly decreased in all barley groups. In mice given barley flour hydrolyzed for 8 hr (PHEB‐8h), blood glucose levels tended to decrease at 30 min when compared with the control group ( p = .06). Total short‐chain fatty acids (SCFA) contents in the cecum were significantly increased in the BF and PHEB groups compared with the control group. Conclusions: We demonstrated that the improving effects of barley β‐glucan on glucose and lipid metabolism were maintained even after partial hydrolysis, whereas the effects of barley β‐glucan on intestinal microbiota and SCFA production were moderately changed by partial hydrolyzation. Significance and novelty: The findings of this study showed that, even after the cooking process, partially hydrolyzed barley β‐glucan is expected to improve glucose and lipid metabolism, similar to intact barley β‐glucan.